Safety and efficacy of Trimax‐360 serum in healthy adult subjects with mild to moderate alopecia of scalp. (10th May 2022) - Chew, Soon‐Keong; Gajjar, Trusha; Sethi, Simran
Abstract: Background: Male pattern baldness and female pattern baldness, commonly known as androgenic alopecia, is the most prevalent type of alopecia, often genetically predetermined. It is a condition of hair loss, which typically affects the scalp and characterized by progressive terminal hair loss. Objectives: The study was conducted to evaluate efficacy and safety of botanical‐based Trimax‐360 Serum in healthy adult subjects with mild to moderate alopecia of scalp. Methods: A total of 30 subjects were randomized in an open label, single arm study conducted in healthy males and females aged 30–45 years. Trimax‐360 Serum was applied twice a day for 98 days to each subject. Effect of Trimax‐360 Serum was evaluated for hair thickness, hair density, scalp condition, hair fall, hair oiliness, softness, and hair growth rate assessment. Results: Statistically significant [ p ‐value <0.0001] improvement was observed in hair density, hair thickness, and hair growth rate after 98 days treatment with Trimax‐360 Serum. The trend of improvement in change from Baseline was gradual from Day 21 to Day 98 which was found to be 1.7%–41.5% for hair density; 0.00 µm to 10.7 µm for hair thickness, respectively. The mean (±SD) hair growth rate (μm/day) also gradually improved from 13.044(±9.4119) to 42.528(±18.5565) μm/day after 21 days to 98 days treatment with Trimax‐360 Serum. All subjects showed good scalp condition and gentle increase in noticeable new hairs while none of the patient reported hair oiliness and hair fall. No apparent adverse events were observed throughout treatment duration. Conclusions: The results of this open label study suggest that 98 days treatment with botanical‐based Trimax‐360 Serum is safe and effective in significantly improving the rate of hair growth.